Metabolomics combined with proteomics analysis of femur provides a comprehensive interpretation of the changes in postmenopausal osteoporosis under salidroside treatment - Yuanyuan Zhai; Xin Li; Yifei Wang; Mengting Gao; Li Feng; Jinjun Shan; Tong Xie; Yudan Cao; Fangfang Cheng; Beihua Bao; Li Zhang; Anwei Ding; et al. (Elsevier, 2022)
Ethnopharmacological relevance: Salidroside (SA), a primary biologically active compound in Fructus Ligustri Lucidi, has a definite effect on anti-aging, a physiological phenomenon that is directly related to postmenopausal osteoporosis (PMOP). However, the mechanisms of treating PMOP of SA have not been comprehensively investigated. Aim of the study: In this study, metabolomics combined with proteomics analysis of femur was established to uncover the detailed molecular mechanism of SA exerted on PMOP. Materials and method: Firstly, we established the mice models of PMOP and detected the changes of biochemical indices in serum and histomorphometric analysis in femur to explore the effects of salidroside (SA) in treating the disease. Then, the gas chromatography-mass spectrometry (GC-MS) based metabolomics and Tandem Mass Tag (TMT) labeled proteomics of femur samples have been developed to find the possible significant metabolites and proteins in PMOP mice and all difference alters were further integrated to find the potential pathways related to PMOP. Next, network analysis was applied to visualize the relationships between identified metabolites and proteins in detail to systematically understand the pathological mechanism of PMOP at a molecular level. Finally, crucial proteins were verified and it might provide a foundation for making out the potential sensitive targets on PMOP. Results: This study demonstrated that SA might prevent the pathological process of PMOP through regulating the disturbed metabolic pathway, including glucose metabolism, lipid metabolism and amino acid metabolism. In addition, the proteins of GLB1 and B4GALT1 were further verified by Western blot and ELISA. Meanwhile, GLB1 as an enzyme related to aging might be a potential marker for PMOP. Conclusion: Our integrated proteomics/metabolomics study of femur samples could contribute to systematically understand the pathological mechanism of PMOP at a molecular level and might provide a foundation for making out the potential sensitive targets of SA on PMOP via anti-aging.